2020
DOI: 10.3390/molecules25061428
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Substitution at Tetracoordinate Sulfur. Kinetics and Mechanism of the Chloride-Chloride Exchange Reaction in Arenesulfonyl Chlorides: Counterintuitive Acceleration of Substitution at Sulfonyl Sulfur by ortho-Alkyl Groups and Its Origin

Abstract: The chloride-chloride exchange reaction in arenesulfonyl chlorides was investigated experimentally and theoretically by density functional theory (DFT) calculations. The second order rate constants and activation parameters of this identity reaction were determined for 22 variously substituted arenesulfonyl chlorides using radio-labeled Et4N36Cl. The chloride exchange rates of 11 sulfonyl chlorides bearing para-and meta-substituents (σ constants from −0.66 to +0.43) in the aromatic ring followed the Hammett eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…The above theoretical results agree well with our recent work [8] regarding the reactivity of arenesulfonyl chlorides and kinetics of the chloride-chloride exchange reaction at the sulfonyl center (Scheme 4). Our DFT studies showed that this reaction proceeds via a single transition state according to the S N 2-mechanism [8].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…The above theoretical results agree well with our recent work [8] regarding the reactivity of arenesulfonyl chlorides and kinetics of the chloride-chloride exchange reaction at the sulfonyl center (Scheme 4). Our DFT studies showed that this reaction proceeds via a single transition state according to the S N 2-mechanism [8].…”
Section: Introductionsupporting
confidence: 91%
“…The above theoretical results agree well with our recent work [8] regarding the reactivity of arenesulfonyl chlorides and kinetics of the chloride-chloride exchange reaction at the sulfonyl center (Scheme 4). Our DFT studies showed that this reaction proceeds via a single transition state according to the S N 2-mechanism [8]. The analogous identity fluoride exchange reaction was found to occur according to the stepwise A-E mechanism and the formation of a transient pentacoordinate sulfurane intermediate.…”
Section: Introductionsupporting
confidence: 91%
“…Quite recently, we were able to solve these fundamental mechanistic questions in parallel studies on nucleophilic substitution at tetracoordinate sulfur [15]. We found that the results of kinetic studies of the chloride-chloride exchange reaction in arenesulfonyl chlorides in combination with the DFT computations of this identity reaction gave convincing evidence for operation of the S N 2-S mechanism with a single transition state.…”
Section: Figurementioning
confidence: 95%